Polymorphisms in the Promoter Region of the Alpha1A-Adrenoceptor Gene Are Associated with Schizophrenia/Schizoaffective Disorder in a Spanish Isolate Population - Clark, Dan A.; Arranz, Maria J.; Mata, Ignacio; Lopéz-Ilundain, Jose; Pérez-Nievas, Fernando; Kerwin, Robert W. (Biological psychiatry (1969), 2005)
Animal models have implicated the α 1-adrenergic subtypes in cognitive functions relevant to schizophrenia, but no consensus exists with regard to the status of noradrenergic receptor populations in psychiatric patients. We focused on one α 1-adrenergic subtype, the α 1A-adrenergic receptor, and proposed that genetic variants within the regulatory region of this gene (ADRA1A) alter the expression of this receptor, influencing susceptibility toward schizophrenia. This study examined this proposal by testing the hypothesis that single nucleotide polymorphisms (SNPs) in the promoter region of the α 1A-adrenergic gene were associated with schizophrenia by performing case–control association analysis on SNPs found in a 5′ upstream region, which included the putative promoter region and 5′ untranslated region. Our sample consisted of 103 schizophrenia and 14 schizoaffective disorder patients and 176 control subjects. All recruits were from a Spanish population isolate of Basque origin that is characterized by low heterogeneity, which was selected with the intent that it might facilitate the identification of disease-related polymorphisms. A total of eight SNPs (−9625 G/A, −7255 A/G, −6274 C/T, −4884 A/G, −4155 C/G, −2760 A/C, −1873 G/A, and −563 C/T) were confirmed at a rare allele frequency of >5%. Association with schizophrenia and schizoaffective disorder was found for the −563 C/T SNP ( p = .0005 for allele and p = .007 for genotype, Bonferroni corrected) and −9625 G/A SNP ( p = .02 for allele and p = .03 for genotype, Bonferroni corrected). Significant differences in the 54 haplotypes formed by these eight SNPs were also found between patients and control subjects ( p = .008, Bonferroni corrected). Because of the strength of these results and the location of these SNPs in the regulatory region of this gene, functional studies investigating the possible influence of these SNPs on receptor expression levels in schizophrenia are warranted.